IMPROVING STUDENT SPEAKING ABILITY THROUGH THE INTEGRATED ENGLISH LESSON METHOD: DEMONSTRATIVE PRESENTATION - Helmy Sahirul Alim (INOVISH JOURNAL, 2018)
The purpose of this study is to know that there will be an improvement in students' speaking skill when they are faced with Demonstrative Presentation. This research will use Classroom Action Research design using three research instruments. The results of research will be conducted in two cycles that show this study is not only able to improve students' speaking ability but also increase active participation of students. The expected results of this study are (1) obviously to find out that this method will increase the ablity of studenst in speaking, the most important that we probably will see additional vocabulary of sign posting in students’ speaking; (2) Another predicted result in this sudy is the possibility of students’ actve participation in the class activity.